Application of Molecular Dynamics to the Investigation of Metalloproteins Involved in Metal Homeostasis. Issue 43 (20th September 2018) - Sala, Davide; Musiani, Francesco; Rosato, Antonio
Abstract : Available estimates indicate that 30–40 % of all proteins need at least one metal ion to perform their biological function. Therefore, they are called metalloproteins. The correct biosynthesis of metalloproteins requires living organisms to be able to cope with issues such as the limited bioavailability or the potential cytotoxicity of several essential metals. Thus, organisms have developed complex machineries that guarantee the proper intracellular concentration and distribution among compartments of each metal, i.e. metal homeostasis. To understand how the different proteins responsible for metal homeostasis carry out their function, it is necessary to investigate their three‐dimensional (3D) structure and mobility at the atomic level. Nuclear magnetic resonance spectroscopy is one of the main experimental techniques providing this information. Computer simulations of molecular dynamics (MD) complement experimental information by showing how the 3D structure fluctuates over time and as a function of environmental conditions, with the possibility of exploring a wider range of timescales and conditions than usually amenable to experiment. Here we review numerous applications of MD for the investigation of the structure and dynamics of metalloproteins, and we also mention some technical aspects related to the parametrization of metals in commonly used force fields. Abstract : Molecular dynamics simulations complement experimental information providing an atomistic view on biological functions. Here we discuss some applications to the study of metalloproteins, from the determination of their 3D structures, to their role in metal storage, transport and metal‐dependent transcriptional regulation. Some technical aspects related to the parametrization of metal ions are also mentioned.